2014
DOI: 10.1590/s0100-736x2014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Freund's adjuvant-induced inflammation: clinical findings and its effect on hepcidin mRNA expression in horses

Abstract: Pesq. Vet. Bras. 34(1):51-56, janeiro 2014 51 hepcidina em equinos.] A hipoferremia observada durante os processos inflamatórios sistêmicos é mediada pela hepcidina. O aumento da expressão da hepcidina é particularmente importante durante a inflamação aguda, por restringir a disponibilidade de ferro necessária para o crescimento de microrganismos patogênicos antes que a imunidade adaptativa ocorra. O objetivo deste estudo foi avaliar os achados clí-nicos e a expressão hepática do RNA mensageiro (RNAm) da hepci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Some AMPs tend to work by sequestration of ions vital for bacterial survival. Hepcidin and Psoriasin reduce the concentration of iron and zinc ions, respectively, and thus restrict the growth of pathogens [ 45 , 46 ].…”
Section: Biological Function and Mode Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some AMPs tend to work by sequestration of ions vital for bacterial survival. Hepcidin and Psoriasin reduce the concentration of iron and zinc ions, respectively, and thus restrict the growth of pathogens [ 45 , 46 ].…”
Section: Biological Function and Mode Of Actionmentioning
confidence: 99%
“…During acute inflammation, the increase in levels of iron supports the growth of pathogens, and hepcidin reduces bacterial survival by restricting the availability of iron. In one study, healthy horses were administered with Freund’s complete adjuvant by intramuscular injection at two-time point, namely, 0 h and 12 h. It was observed that 6 h post-infection, hepcidin mRNA increased and remained high until 18 h. The plasma iron concentration decreased significantly between 16 h and 72 h post-infection as compared to control, suggesting the role of hepcidin in the rapid onset of hypoferremia to restrict the availability of iron for the growth of pathogens [ 45 ]. Overexpression of hepcidin in transgenic mice resulted in decreased body iron levels and severe microcytic hypochromic anemia, confirming its role in iron sequestration is central to its activity [ 110 ].…”
Section: Equine Ampsmentioning
confidence: 99%
“…It was observed that 6h post-infection, hepcidin mRNA increased and remained high till 18h. The plasma iron concentration decreased significantly between 16h and 72h post-infection as compared to control, suggesting the role of hepcidin in the rapid onset of hypoferremia to restrict the availability of iron for the growth of pathogens (Oliveira-Filho et al, 2014). Overexpression of hepcidin in transgenic mice resulted in decreased body iron levels and severe microcytic hypochromic anaemia, confirming its role in iron sequestration and central to its activity (Nicolas et al, 2002).…”
Section: Equine Hepcidinmentioning
confidence: 84%
“…Some AMPs tend to work by sequestration of ions, which are necessary for bacterial survival. Hepcidin and Psoriasin reduce the concentration of iron and zinc ions, respectively, and thus restrict the growth of pathogens (K. C. Lee and Eckert, 2007;Oliveira-Filho et al, 2014).…”
Section: Biological Function and Mode Of Actionmentioning
confidence: 99%
“…Due to this its feature, FCA has used frequently in animal studies for monitoring changes related to inflammation. In this context, an inflammatory reaction induced by FCA has been shown to occur in rabbits (Fishback et al, 2016), mice (Ferreira et al, 2001;Chillingworth and Donaldson, 2003), horses (Mills et al, 1998;Oliveira-Filho et al, 2014), and dogs (Botrel et al, 1994;Haak et al, 1996). It is reported that the inflammatory reaction may occur with FCA application in sheep as in other animal species (McClure et al, 1991;Badial et al, 2011).…”
Section: Discussionmentioning
confidence: 99%